Measurement of vascular function in haemodialysis and obese patients by myography - Abushufa, Adil (2013)
Background: Patients with chronic kidney disease (CKD) face a markedly increased risk of cardiovascular morbidity and mortality. In this setting, aberrant endothelial function is a key initiating event in vascular disease. Haemodialysis (HD) patients characteristically exhibit significant abnormalities in vascular structure and function, which impact cardiovascular morbidity and mortality. Micro- and macro-vascular dysfunctions are the principle factors contributing to the increased risk of morbidity and mortality associated with obesity. Impaired endothelial function represents the earliest abnormality in the development of vascular disease in obesity and exhibits increased risk of cardiovascular disease. We first aimed to investigate the effect of HO and obesity on the vascular reactivity through directly examines the isolated subcutaneous arteries using wire myography. The second goal was to study changes that might underlie altered vascular responses following bariatric surgery and whether reduction in weight improves endothelial function. We also intended to correlate the ex vivo myography data with the in vivo results of pulse wave velocity (PWV) and blood pressure (BP) in both HO and obese patients. Methods: Abdominal subcutaneous fat biopsies were obtained from HO patients (n= l l ) during non-HO visits through small lower abdominal incisions using local anaesthetics; obese patients (n=12) during the time of bariatric surgery (using a laparoscopic port); and non-HD, non-obese healthy controls (n=26) during the time of elective surgery (hernia repair). Additional abdominal subcutaneous fat samples (n=4) were also obtained from obese patients at six months after bariatric surgery through an extra incision in the lower abdominal region using local anaesthetics. Different-sized arteries (small with internal diameter between 200 urn - 500 urn and large between 600 urn - 900 urn) were dissected, mounted and conducted on a wire myography on the same day. Cumulative concentration-response curves were constructed for the following vasoactive agents: noradrenalin (NA), endothelin-I (ET-I), U46619, angiotensin II (AngII), vasopressin, bradykinin (BK), acetylecholine (Ach) and sodium nitroprusside (SNP). Carotid-to-femoral arterial PWV was measured using an oscillometric device (Vicorder, Skidmore Medical Ltd., UK) for HD and obese patients in addition to measuring blood pressure (BP). Laboratory data were expressed as mean ± SEM and groups were compared by t-test. Results: In both HD and obese patients, greater contractile response to different vasoconstrictors was observed in different-sized arteries compared to control group. Although the potency of these drugs was similar between HD patients and controls, large vessels of HD patients were highly potent to U46619 and vasopressin compared to controls. Similarly, in obese patients, large vessels were also significantly more sensitive to U46619 and vasopressin than that of controls, while small vessels were highly potent to vasopressin response. The maximum vasorelaxation response of small and large vessels to Ach and BK (endothelium-dependent vasodilators) was significantly lower in both HD and obese patients than vessels of controls. A similar response to SNP (an endothelium-independent vasodilator) was obtained in all groups. However, the potencies of all vasodilators in all groups were similar. In HD patients, in vivo PWV was significantly correlated with the maximum contractile response of large arteries to vasopressin response (r = 0.829, P = 0.042). PWV was positively correlated with the percentage of maximum contractile response of small arteries to vasopressin (r = 0.886, P = 0.019). The diastolic but not systolic BP of HD patients was significantly inversely correlated with the response of large vessels to SNP (r = -0.954, P = 0.012), it was also negatively correlated with the percentage of contractile response of small arteries to vasopressin (r = -0.829, P = 0.042). There was no correlation observed in the responses of isolated small arteries to the other vasoconstrictor substances in terms of PWV or BP. In obese patients, The PWV was significantly correlated with the maximum contractile response of large arteries to U46619 (r = 0.928, P = 0.006), and with the maximum contractile response of small arteries to vasopressin (r = 0.885, P = 0.033).However, positive correlation was obtained between systolic (but not diastolic BP) of obese patients and the response of large vessels to U46619 (r = 0.785, P = 0.048). There was no significant difference in the vasocontractile or vasorelaxation responses of isolated vessels in obese patients before and after surgery; however, a trend of more contractile response to vasoconstrictors was observed in the obese group before surgery compared to those after surgery. Conclusion: These results suggest that HO and obesity can alter endothelial function via an incremental increase in vasocontractility in response to various stimuli and an impaired vasodilatation response to endothelium-dependent agonists in isolated different-sized vessels. In both groups, ex vivo arterial responses were correlated to in vivo assessment of arterial function. The association between these risk groups and endothelial dysfunction in isolated arteries would be expected to accelerate cardiovascular events, which impacts cardiovascular morbidity and mortality among these groups of patients. Therefore. the development of cardiovascular disease is mediated, at least partly, by functional alterations at the level of microcirculation.